The Indian National Congress and political mobilisation in the United Provinces, 1926-1934 - Pandey, G (1975)
﻿ Recent studies of the development of Indian politics in the nineteenth and twentieth centuries have contested the notion of a giant clash between imperialism and nationalism in the sub-continent. Increasingly, these studies have focused on the regional variations of the Indian national movement, and high-lighted the contradictions within it. Not only has the earlier vision of the unity of the movement tended to break down as a result. The very continuity and indeed existence of the movement has apparently been brought into question. Yet the strength of something perceived as a nationalist movement by large numbers of contemporary observers, official and non-official, has been undoubted. To meet this difficulty, historians have sought to re-introduce by new methods some element of continuity and permanence into their concept of the Indian nationalist movement. An important suggestion has been that the links between different levels of politics, different regions and different interests were provided by the formal political structure imposed on the country by the British. Constitutional development, then, accounts for an on-going national movement, and changes in the constitutional set-up explain changes in the intensity, scale and form of the nationalist struggle. One problem with these studies has been the almost invariable concentration on 'elites' and the leadership. Differences among nationalist leaders have been taken as indicative of the contradictions within the nationalist movement. Links between leaders have appeared as nationalist links. 'Followers', it has generally been assumed, acted simply in accordance with the wishes of their leaders. The present thesis concentrates much more on the relationship between leaders and followers in the national movement. It investigates the means of communication between them, the barriers and the contradictions, and tries to assess the way in which leaders and followers influenced one another and 'followers' occasionally became leaders in their own right. An attempt is also made to explain the continuity of the national movement, in terms not only of the changing constitutional structure, but also of the permanent organisational base of the movement and the independent power that nationalist propaganda, symbols and slogans - broadly speaking, the nationalist 'ideology' - came to have. Finally, the thesis examines how the method and manner of nationalist propaganda, as well as the institutions and style of British rule, tended to divide sections of the Indian 'nation' from one another, and how the Congress leadership responded when these divisions assumed dangerous proportions. The striking fact is that as the Congress-led movement for freedom advanced to a position of enormous strength, its weaknesses also became more obvious. The Introduction sets out this problem in the case of the United Provinces of Agra and Oudh, (U.P.), an area noted for its prominence in the national movement after the First World War. It shows how by the early 1930's the Congress was recognised as the strongest and most organised party in the province, and one that constituted a real threat to the position of the Government. Yet this party had the active support neither of the Muslim community in general nor of the mass of the poor in town and country. The chapters that follow seek to explain the genesis of this apparently paradoxical position. Chapter 2 examines the organisational base of the Congress movement in the 192O's and early 193O's. It is suggested that in the years immediately after World War I a sound base was secured, through the presence of a hard core of permanent workers in the organisation, financial support from business, industrial and other sympathetic groups, and the work of 'national' educational and other institutions which provided new recruits for nationalist activity. The weakness of the organisation is seen in its failure to make any direct provision for the poorer sections of Indian society. Some attempt was made to remedy this situation in the last years of the period under study, but it is argued that these were piecemeal and limited efforts which did not go very far. Chapter 3 elaborates the very broad, nationalist appeal made by the Congress, the agencies it used and the effects of its endeavours. It is shown that personal contact, acts of 'revolutionary terrorism' and the press, all performed valuable propaganda for the nationalist cause. Racial and religious elements in the Congress' propaganda had widespread influence. There was room also for appeals on specific economic issues within the general, nationalist approach of the Congress. Where the Congress approach confronted major problems was at points where parts of its appeal brought different sections of the society into clash with one another. The remaining chapters examine the limitations that this, and the Congress' refusal to face the problem squarely, imposed on the movement as a whole. Chapter 4 makes a case-study of pppular agitation during the civil disobedience campaign in two very different U.P. districts, one in Agra and the other in Oudh. This indicates how the Congress encouraged popular agitation and yet tried to keep it under strict control. The chapter argues that the Congress attempt to maintain the broadest possible front in its anti-imperialist struggle misfired at this point. Large numbers of peasants, extremely distressed on account of the conditions created by the Depression and agitated at the relentless efforts of the Government and the landlords to extract their dues, strained at the leash that Congress leaders had tied on them regarding the manner of their protest. Friction between the two was especially marked when the Congress withdrew the 'no-tax'/'no-rent' campaign after the Gandhi-Irwin agreement of March 1931. Ultimately, the chapter suggests, the obvious distress of large sections of the peasantry and the independent actions of angry tenants led the Congress to adopt a more militant position, but before then the hesitations of the leadership had caused a substantial loss of support for civil disobedience. Chapter 5 turns to the problem of the alienation of the Muslims from the national movement, a fact that was clear at least in the U.P. by the time of the civil disobedience movement, fhe importance of the style of British rule, and of the nature of electoral arrangements, is noted. But the chapter is concerned more with the manner in which sectional appeals, adopted for short-term electoral or agitational purposes, contributed to the growth of communal antagonism. The importance of communal tension on the ground in the development of a separate Muslim politics is emphasized. By the end of the 192O's, it is suggested, general communal suspicion had made it difficult for Hindu and Muslim leaders to work together, and subsequent attempts by Congress (Hindu) leaders to appeal to the Muslim 'masses' over the heads of Muslim leaders only tended to close Muslim ranks further. A central theme of the thesis is that the general nationalist appeal of the Congress proved a source both of strength and of weakness for the movement. Aggressive anti- British propaganda gave rise to the widespread view of the Raj as enemy and oppressor. Racial clashes between Government forces and nationalist deroonstrators proved particularly important in arousing anti-British feeling among very diverse groups and people. In addition, the Congress after 192O acquired the image of the 'poor man's party'. It is seen, however, that nationalist symbols and slogans, which were widely accepted, had vary different meanings for different people. The extension of a 'national', or at least an anti-British consciousness to social groups which had been unaffected earlier led to Increasing conflicts of interest within the nationalist camp. It was at this point that the Congress' broad, nationalist platform proved a stumbling block. The leadership was reluctant to make any clear choices. Instead, there was a piecemeal and hesitant response to each new situation of crisis. One important reason for this, it is argued,, was the class composition of the Congress leadership and cadres which prevented the adoption of any very radical position- Another contributory factor was that, while there was a clear notion in the Congress camp about the ultimate political goal, there was a complete lack of clear thinking on the major social and economic questions that might be confronted on the way to that goal, or after its attainment. It was only on account of the building up of a variety of pressures during the period under study - the extreme demands of distressed peasant groups, the militancy of students and other young men and women, the sullen resentment of Muslim leaders and 'masses', and the constitutional initiatives of the British - that the Congress leadership began to spell out its programme more fully. In the process, both the areas of strength and the areas of weakness of the national movement increased. The concluding chapter draws together these arguments.